Sixty-five papyrological texts : presented to Klaas A. Worp on the occasion of his 65th birthday - Hoogendijk, F. A. J.; Muhs, Brian Paul; Bakker, M. J.; Worp, K. A. (Klaas Anthony) (Papyrologica Lugduno-Batava ;, 2008)
Contains editions of sixty-five Greek, Demotic, Coptic and Arabic texts from Egypt, contributed as a token of friendship and respect by forty-six of Klaas Worp's colleagues and co-authors upon his retirement from the Papyrological Institute of the University of Leiden in August 2008.